Evaluation of combined utilization of marble dust powder and fly ash on the properties and sustainability of high‑strength concrete - Ahmed Rid, Zaryab; Raza Shah, Syed Naveed; Memon, Muhammad Jafar; Jhatial, Ashfaque Ahmed; Keerio, Manthar Ali; Wan, Inn Goh (Springer Link, 2022)
With the recent increase in demand for high-strength concrete, higher cement content is utilized, which has increased the need for cement. The cement industry is one of the most energy-consuming sectors globally, contributing to 10% of global carbon dioxide (CO2) gas emissions and global warming. Similarly, with rapid urbanization and industrialization, a vast number of by-products and waste materials are being generated in abundance, which causes environmental and health issues. Focusing on these two issues, this study aimed to develop an M50-grade eco-friendly high-strength concrete incorporating waste materials like marble dust powder (MDP) and fy ash (FA) as partial cement replacement. 2.5%, 5%, 7.5%, and 10% MDP and FA by weight of total binder was utilized combinedly, such that the 5%, 10%, 15%, and 20% cement content was replaced, respectively. The fresh state properties in terms of workability and hardened state properties in terms of compressive and fexural strengths were evaluated at 7, 14, 28, 56, and 90 days. Furthermore, to assess the environmental impact of MDP and FA, the embodied carbon and eco-strength efciency were calculated. Based upon the results, it was observed that a combined 10% (5% MDP and 5% FA) achieved the highest strength; however, 15% (7.5% MDP and 7.5% FA) substitution could be optimal. Furthermore, the combined utilization of FA and MDP also enabled a reduction in the total embodied carbon. It decreased the cost of concrete, resulting in an eco-friendly, high-strength concrete.